Analisis Kecakapan Mahasiswa Fakultas Dirasatislamiyyah UIN Syarif dari Imla' Dosen dalam Penerapan Hamzah Wasol dan Hamzah Qot': Analisis Kecakapan Mahasiswa Fakultas Dirasatislamiyyah UIN Syarif dari Imla' Dosen dalam Penerapan Hamzah Wasol dan Hamzah Qot' - Daud Lintang; Juwika Afrita (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2023)
This study aims to analyze the proficiency of students at the Faculty of Dirasatislamiyyah UIN Syarif in applying Hamzah Wasol and Hamzah Qot' and to examine the extent to which the imla' of lecturers influences students' proficiency. This study uses a qualitative descriptive method with purposive sampling technique. Data were collected through written tests and interviews with students as well as direct observation of the imla' of lecturers. The results of the study show that the proficiency of students in applying Hamzah Wasol and Hamzah Qot' still needs to be improved, and the imla' of lecturers has a positive effect on students' proficiency in applying both hamzahs. This indicates that the role of lecturers is very important in helping to improve students' ability to learn Arabic.